Left ventricular dysfunction and coronary artery bypass grafting. - Amaury Flores Sánchez; Arlenis Rodríguez Martínez; Marcela Patricia Castillo Martínez (Revista Cubana de Cardiología y Cirugía Cardiovascular, 2015)
Patients with ischemic cardiomyopathy have high risk in a short period of time after surgery and improvement of survival for a long time. It is necessary counterbalance the higher risk in the short period of time after surgery and posterior benefits. This  bibliographic review was done with the purpose of knowing novel aspects about advantages and disadvantages of coronary artery bypass grafting in patients with left ventricular systolic dysfunction. Articles linked to theme and disposable in the last 8 years in Database like CUMED and PubMed/Medline were reviewed.Information was condensed, analyzed and resumed. Coronary surgery is associated with less cardiovascular mortality, hospitalizations for heart failure, improvement of functional class and quality of life. Higher risk immediately after coronary surgery is counterbalanced with the improvement of patients in postsurgical middle time and longtime. Coronary artery bypass grafting is very useful in patients with left ventricular systolic dysfunction.